Telomere length and COVID-19 disease severity: insights from hospitalized patients - Vos, Stijn; Martens, Dries S.; De Waele, Elien; Dewyspelaere, Geert; Mistiaen, Geert; Goeminne, Pieter; Nawrot, Tim S. (Frontiers in Aging, 2025)
IntroductionTelomere length is associated with various disease and immune function and may therefore impact COVID-19 disease severity. We studied the associations between telomere length as a geroprotective susceptibility marker and clinical outcomes in hospitalized COVID-19 patients.Methods283 hospitalised COVID-19 patients (before vaccination, recruited between May 2020 and March 2021) were recruited for this cross-sectional study. Blood telomere length was determined by qPCR. The association between blood telomere length and clinical outcomes was examined using logistic regression, while adjusting for various covariates and confounders including demographic factors, comorbidity, body-mass index and blood cell counts. The primary clinical outcomes assessed were duration of stay, risk of ICU admission, and risk of requiring ventilation support.ResultsIndependent of sex and chronological age, an interquartile-range (IQR) increase in blood telomere length was associated with more favourable clinical outcomes in hospitalised COVID-19 patients: specifically, the odds ratio for ICU admission was 0.55 (95%CI: 0.32–0.88). Moreover, the odds ratio for the risk of ventilation was 0.52 (95%CI: 0.31–0.84). Finally, ordinal logistic regression revealed a lower odds for being in a higher quantile of hospital duration (OR: 0.79, 95%CI: 0.58–1.06).DiscussionTo conclude, we found that in hospitalised COVID-19 patients, longer telomeres was associated with lower diseases severity in hospitalised COVID-19 patients, that could not be explained by shifts in blood cell counts. Therefore supporting the geroprotective or immunoprotective effects associated with longer telomeres conferring lower susceptibility to severe COVID-19 outcomes.